Low temperature transport properties of pyrolytic graphite sheet. (September 2017) - Nakamura, Sachiko; Miyafuji, Daisuke; Fujii, Takenori; Matsui, Tomohiro; Fukuyama, Hiroshi
Highlights: We characterized transport properties of Pyrolytic Graphite Sheet (PGS). Thinner PGS has higher crystallinity and higher electrical/thermal conductivities. Electrical and thermal conductivities of graphite-family have some relationship. PGS is advantageous for applications as a thermal link at 60–300 K. Abstract: We have made thermal and electrical transport measurements of uncompressed pyrolytic graphite sheet (uPGS), a mass-produced thin graphite sheet with various thicknesses between 10 and 100 μ m, at temperatures between 2 and 300 K. Compared to exfoliated graphite sheets like Grafoil, uPGS has much higher conductivities by an order of magnitude because of its high crystallinity confirmed by X-ray diffraction and Raman spectroscopy. This material is advantageous as a thermal link of light weight in a wide temperature range particularly above 60 K where the thermal conductivity is much higher than common thermal conductors such as copper and aluminum alloys. We also found a general relationship between thermal and electrical conductivities in graphite-based materials which have highly anisotropic conductivities. This would be useful to estimate thermal conductance of a cryogenic part made of these materials from its electrical conductance more easily measurable at low temperature.